The temperature dependence of the band GAPSi - Guliamov, G.; Erkaboev, U.I.; Sharibaev, N.Y. (Физическая инженерия поверхности, 2013)
With the help of mathematical modeling of the thermal broadening of the energy levels studied the temperature dependence of the band gap semiconductors. In view of the temperature dependence of the effective mass of the density of states obtained graphs temperature dependence of the band gap. Investigated the effect of changes in the effective mass of charge carriers on the temperature dependence of the band gap semiconductors. The theoretical results of mathematical modeling are compared with experimental data for Si. The theoretical results satisfactorily explain the experimental results for Si.